Experimental Verification of Strut-and-Tie Model Design Method - Ley, M. Tyler; Riding, Kyle A.; Widianto; Bae, Sungjin; Breen, John E. (My University, 2010)
Strut-and-tie models (STM) are a valuable tool for the design of irregular concrete members. This paper presents the experimental results of tests conducted on small-scale, simply supported dapped beams with openings under the load. The design of each test specimen was developed by independent student teams using the ACI 318-05 provisions for STM. An unreinforced specimen was also constructed for comparison. Each reinforced specimen resisted loads greater than the factored design load and exhibited little distress at service load levels. Examination of the behavior of each model permits appraisal of the design model used by each design team. These results show the STM to be a conservative, lower-bound design approach that allows the designer a great deal of flexibility.
Keywords: Bearings; Size effect; strut-and-tie modeling